2020
DOI: 10.1021/acsami.0c15509
|View full text |Cite
|
Sign up to set email alerts
|

Control of Molecular Orientation of Spiro-OMeTAD on Substrates

Abstract: 2,2′,7,7′-Tetrakis(N,N-di-p-methoxyphenylamino)-9,9′-spirobifluorene (spiro-OMeTAD) is utilized as a p-type semiconductor layer in perovskite solar cells and solid-state dye-sensitized solar cells. Spiro-OMeTAD has been known to have a spiro center, leading to a random orientation. Although the molecular orientation of organic semiconductor materials influences the conductivity, which is directly related to semiconductor device characteristics, the molecular orientation of spiro-OMeTAD has not been fully discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…The distance of π-π stacking structure and the lamellar structure was calculated to be 3.70 and 22.5 Å, respectively. These results indicate that PDTDT has a predominant face-on orientation, [14] which is favorable for hole transport in PSCs. Using the space-charge limited current (SCLC) method (Figure S1c, Supporting Information), the hole mobility of PDTDT was calculated to be 3.14 × 10 −3 cm 2 V −1 s −1 , which is higher than P3HT (1.67 × 10 −3 cm 2 V −1 s −1 ), as well as poly(DTSTPD-r-BThTPD) (1.50 × 10 −3 cm 2 V −1 s −1 ).…”
Section: Resultsmentioning
confidence: 81%
“…The distance of π-π stacking structure and the lamellar structure was calculated to be 3.70 and 22.5 Å, respectively. These results indicate that PDTDT has a predominant face-on orientation, [14] which is favorable for hole transport in PSCs. Using the space-charge limited current (SCLC) method (Figure S1c, Supporting Information), the hole mobility of PDTDT was calculated to be 3.14 × 10 −3 cm 2 V −1 s −1 , which is higher than P3HT (1.67 × 10 −3 cm 2 V −1 s −1 ), as well as poly(DTSTPD-r-BThTPD) (1.50 × 10 −3 cm 2 V −1 s −1 ).…”
Section: Resultsmentioning
confidence: 81%
“…S25 and S26). A straightforward possibility for inducing the WF change is the introduction of a macroscopic dipole, which could be induced either by a particular spiro-OMeTAD orientation ( 45 ) or by an interfacial TBMP + TFSI – accumulation ( 46 ). We excluded the former on the basis of the grazing-incidence wide-angle x-ray scattering (GIWAXS) results (fig.…”
Section: The Mechanism Of Ionic Salts Modulating Spiro-ometad Dopingmentioning
confidence: 99%
“…These findings are interesting when compared to the data reported by Shibayama et al who observed some orientation of Spiro‐OMeTAD layers when deposited on certain substrates (i.e., Si, FTO, nickel oxide, and perovskite layers). [ 43 ] They demonstrated there is variation in Spiro‐OMeTAD behavior from substrate to substrate and they suggested that Spiro‐OMeTAD orientation was influenced by substrate surface energy. However, their study did not investigate Spiro‐OMeTAD deposited on TiO 2 and so the authors believe the data reported here are the first reported on this substrate.…”
Section: Resultsmentioning
confidence: 99%